2018
DOI: 10.3847/1538-4357/aaa0d2
|View full text |Cite
|
Sign up to set email alerts
|

The Physics of Protoplanetary Dust Agglomerates. X. High-velocity Collisions between Small and Large Dust Agglomerates as a Growth Barrier

Abstract: In a protoplanetary disk, dust aggregates in the µm to mm size range possess mean collision velocities of 10 to 60 m s −1 with respect to dm-to m-size bodies. We performed laboratory collision experiments to explore this parameter regime and found a size-and velocity-dependent threshold between erosion and growth. By using a local Monte Carlo coagulation calculation and complementary a simple semi-analytical timescale approach, we show that erosion considerably limits particle growth in protoplanetary disks an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 32 publications
1
44
0
3
Order By: Relevance
“…Again for similar impact velocities, but much smaller projectile aggregates or dust monomers, the effect of erosion has been identified in the laboratory (Schräpler and Blum 2011;Schräpler et al 2018) and by numerical simulations (Seizinger et al 2013;Krijt et al 2015). The erosion efficiency increases with increasing impact velocity and decreases with increasing impactor mass, so that there is a smooth transition to cratering.…”
Section: -Erosionmentioning
confidence: 66%
“…Again for similar impact velocities, but much smaller projectile aggregates or dust monomers, the effect of erosion has been identified in the laboratory (Schräpler and Blum 2011;Schräpler et al 2018) and by numerical simulations (Seizinger et al 2013;Krijt et al 2015). The erosion efficiency increases with increasing impact velocity and decreases with increasing impactor mass, so that there is a smooth transition to cratering.…”
Section: -Erosionmentioning
confidence: 66%
“…Infolgedessen prallen die Staubagglomerate inelastisch voneinander ab, was dann auch dazu führt, dass sie verhältnismäßig kompakt werden, weil ein Teil der Stoß energie in plastische Verformung geht. Obwohl weitere Experimente mögliche Wege aufgezeigt haben, über diese Abprallbarriere hinwegzukommen, sind wir heute recht sicher, dass andere Effekte das weitere Wachstum verhindern: Größere Agglomerate zerstören sich gegenseitig im Stoß, oder sehr kleine Partikel erodieren die großen Agglomerate [6]. Außerdem sollten größere Staubklumpen wegen der sehr raschen radialen Drift in die inneren Bereiche der PPD nur für sehr kurze Zeit existieren, bevor sie so nahe an den Zentralstern geraten, dass sie verdampfen.…”
Section: Zusammenstöße Von Staubteilchenunclassified
“…Glücklicherweise besitzen wir mit den Erkenntnissen der Europäischen Raumsonde Rosetta so viele aus der Nähe gewonnene Daten über den Kern des Kometen 67P/ Tschurjumow-Gerassimenko, dass wir den Versuch starten können, darin nach den Entstehungsbedingungen zu suchen (Physik in unserer Zeit 2016, 47 (6) erklärt werden können, wenn der Kometenkern aus Staubagglomeraten im Größenbereich zwischen 6 und 12 mm Durchmesser besteht [11].…”
Section: Planetesimale Im Heutigen Sonnensystemunclassified
“…While this is desirable in order to perform well-controlled simulations, it is far from reality; Mathis et al (1977) showed that dust grains obey a power-law distribution, the Mathis-Rumpl-Nordsieck (MRN) distribution, rather than a monodisperse distribution. More recent collision experiments on millimeter-sized granular aggregates, which employ polydisperse grain distributions and non-spherical grain shapes, sieve their material in order to obtain narrow size distributions (Whizin et al 2017;Katsuragi & Blum 2018;Schräpler et al 2018). In addition, outside of an astrophysical context, simulations of polydisperse granular material are rare.…”
Section: Introductionmentioning
confidence: 99%